Warner's fantastic 4. - The Corrs; Madonna; Stewart, Rod; Collins, Phil; WARNER Music (Malaysia). (Kuala Lumpur : Warner Music (Malaysia), 1998)
Contains four tracks from four different artists.
CD 1 : Don't Say You Love Me / The Corrs (4:39) -- Power Of Good Bye / Madonna (4:13) -- Shelly My Love / Rod Stewart (3:38) -- True Colours / Phil Collins (3:51).
Koleksi Khas Wiramanja.
The Corrs, Madonna, Rod Stewart, Phil Collins.
Title from disc label.
Keywords: Songs, English; Popular music